SOSIALISASI APLIKASI INFO BMKG DI KANTOR DINAS PERHUBUNGAN KOTA BEKASI - Eko Widyantoro HS; Ade Sekarningsih; Andriana Dwi Hastanto; Andrie Febriansyah; Puji Lestari; Sarnubih Hasan; Warno Mulud; Tukiyat (Abdi Jurnal Publikasi, 2025)
Global climate change, which has triggered an increase in extreme weather events, has had a significant impact on transportation activities in urban areas, including Bekasi City. Low digital literacy and minimal use of the BMKG Info application mean that local government officials are not optimally utilizing meteorological data to support transportation safety. This Community Service (PKM) activity was carried out by Master of Informatics Engineering students from Pamulang University in collaboration with the BMKG and the Bekasi City Transportation Agency. The goal was to increase participants' understanding of the functions and benefits of the BMKG Info application through outreach activities, live demonstrations, and interactive discussions. The results of the activity showed a significant increase in participants' knowledge of weather, climate, and earthquake information, as well as increased awareness of the importance of extreme weather preparedness. This activity also strengthened collaboration between academics and government agencies in developing digital disaster literacy.